OPTIMIZING AI ASSISTANCE IN THE PROCESS OF ENGLISH WRITING: A TAIWANESE PARADIGM OF FACILITATING AI-ASSISTED EFL WRITING TRAINING - Yu-Tien Ho (PUPIL: International Journal of Teaching, Education and Learning, 2025)
In the past decade, automated correction has become increasingly integrated into EFL writing pedagogy, especially with the vast advancement of AI-assisted software. This study looks at how Wordtune, as an AI tool, can facilitate the writing process of intermediate-level EFL students at the Department of Applied Foreign Languages, Tatung University in Taiwan. The selection of Wordtune in this research targets a major challenge for Taiwanese learners that I have been observing for years in my EFL writing classes, namely, their tendency to write generalizations without specific details due to their Chinese ways of thinking, regardless of what genres they are writing. With an AI tool such as Wordtune, students are more likely to get instant feedback on the language scaffolding in their writing process in order to communicate more effectively, as long as AI has been used wisely and ethically. The study analyses how the facilitation of Wordtune helps the paragraph structure and idea development of 25 students across five writing genres: narration, description, classification, cause and effect, and problem-solution. A comparative analysis was conducted between self-revised and AI-enhanced versions of students’ writing. Results indicate that the implementation of Wordtune as an AI tool, together with proper instruction, raised metacognitive awareness of their writing problems. The findings highlight the potential of AI to support intermediate EFL learners in overcoming L1 interference and improving the coherence and specificity of their writing.